Investigating the Convergence Clubs among Provinces of Iran during 2000-2009 - Leila Gholami Heydariani; Reza Ranjpour; Mohammadali Motafaker Azad; Zahra Karimi Takanloo (پژوهشهای اقتصادی, 2014)
The convergence hypothesis is a result of the neoclassical growth model. By definition, the concept of convergence is the faster growth of regions (economies) with lower per capita income compared to the regions (economies) with higher per capita income. This paper deals with convergence clubs among provinces of Iran during 2000-2009. For this purpose, the Panel unit root tests have been used to examine the convergence hypothesis after classifying the provinces with cross-sectional methods. The research results show that Iran’s provinces can be classified into two groups of provinces: (1) ones with low per capita income (18 provinces) and (2) ones with high per capita income (12 provinces). According to the panel unit root tests, the existence of absolute convergence (tendency to a certain standard) between two mentioned groups is confirmed. So, the convergence clubs hypothesis is verified among the Iran’s provinces.